Frequency of human toxocariasis in a rural population from Cajamarca, Peru determined by DOT-ELISA test - Roldán, William H.; Espinoza, Yrma A.; Huapaya, Pedro E.; Huiza, Alina F.; Sevilla, Carlos R.; Jiménez, Susana (Revista do Instituto de Medicina Tropical de São Paulo, 2009)
The aim of this study was to estimate the frequency of human toxocariasis in Cauday district, Cajamarca, Peru, using a dot-ELISA test. From June to October 2005, a total of 256 adult subjects were studied. Blood samples were collected for serology by a dot-ELISA test and for hematological examination. Parasitological examination was also carried out in stool samples to check cross-reactions in the dot-ELISA. The frequency observed was 44.92%, with a significant higher proportion of positivity in male subjects. From subjects with positive serology, 45.6% had respiratory symptoms, 40.44% abdominal pain, 32.35% hepatic symptoms, 14.7% cutaneous signs, 13.23% ocular manifestations, 43.38% eosinophilia, and all of these were statistically associated to serology. Among the population evaluated, 90.23% (231/256) were parasitized. From subjects with positive serology, 92.17% had at least one intestinal parasite and the most frequent were: Blastocystis hominis (68.38%), Giardia lamblia (28.68%), Hymenolepis nana (20.0%), Ascaris lumbricoides (15.65%), Entamoeba histolytica/E. dispar (13.24%), Cyclospora cayetanensis (4.41%), Cryptosporidium sp. (1.47%), Enterobius vermicularis (0.87%), Strongyloides stercoralis (0.87%), Taenia sp. (0.87%), and Trichuris trichiura (0.87%). The rate of false positives in the dot-ELISA test was improved by serum absorption each with A. suum antigens, with a decrease of cross-reactions. In conclusion, human toxocariasis is highly frequent in this population and some risk factors like dog/cat ownership, presence of pets within house, and previous history of geophagia were observed in the present study.